O-GlcNAcylation and cardiovascular disease. (13th April 2017) - Wright, JaLessa N.; Collins, Helen E.; Wende, Adam R.; Chatham, John C.
Abstract : The post-translational modification of serine and threonine residues of proteins found in numerous subcellular locations by O -linked N -acetylglucosamine ( O -GlcNAc) is emerging as a key mediator of many cardiovascular pathophysiological processes. Early studies implicated increased protein O-GlcNAcylation as contributing to the cardiovascular complications associated with diabetes, whereas subsequent studies demonstrated that acute increases in O -GlcNAc levels were protective against ischemia/reperfusion injury. There is now a growing understanding that O -GlcNAc modification of proteins influences numerous cellular functions, including transcription, protein turnover, calcium handling, and bioenergetics. As a result, a more nuanced view of the role of protein O-GlcNAcylation in the cardiovascular system is emerging along with the recognition that it is required for normal cellular function and homeostasis. Consequently, the impact of changes in O -GlcNAc cycling due to stress or disease on the heart is complex and highly dependent on the specific context of these events. The goal of this review is to provide an overview of some of the more recent advances in our understanding of the role O-GlcNAcylation plays in mediating cardiovascular function and disease.